Karakterisasi Asap Cair Hasil Pirolisis Dengan Penambahan Zeolit Dari Limbah Potongan Rambut Manusia - Doliwa, Jihan A; Anom, I Dewe Ketut; Karundeng, Marlina (General Chemistry Journal, 2024)
Pieces of human hair are one type of rubbish that can be found in various places. Human haircut waste has not been widely used, most of this waste is thrown away or burned. The aim of this research is to convert human haircut waste into liquid smoke, analyzing the physical and chemical properties of liquid smoke from human haircut waste. The results of observations of pyrolysis of human hair cuttings were carried out by heating at temperatures ranging from 800C to 2900C. Zeolite in the pyrolysis process can provide fast and stable temperature propagation. The characteristics of liquid smoke resulting from pyrolysis of human hair clippings are: density 0.9552 g/ml, viscosity 5.2759 cSt, heating value 8,461 cal/g, flash point 33.70C, smoke point 178.20C and boiling point 145.00C. KG-SM analysis of liquid smoke resulting from pyrolysis of human hair clippings produced 24 compound peaks.